2009
DOI: 10.1117/1.3122775
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescent immunolabeling of cancer cells by quantum dots and antibody scFv fragment

Abstract: Semiconductor quantum dots (QDs) coupled with cancer-specific targeting ligands are new promising agents for fluorescent visualization of cancer cells. Human epidermal growth factor receptor 2/neu (HER2/neu), overexpressed on the surface of many cancer cells, is an important target for cancer diagnostics. Antibody scFv fragments as a targeting agent for direct delivery of fluorophores offer significant advantages over full-size antibodies due to their small size, lower cross-reactivity, and immunogenicity. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 28 publications
0
17
0
Order By: Relevance
“…They also designed a scFv-(barnasebarnase) fusion protein (termed 'dibarnase'), in which two barnase units were directly fused head-totail without a linker. This module allowed binding of the scFv Ig to the QDs [61]. Taken together, data has shown that the barnase-barstar system constitutes a useful tool for the design of oligomeric proteins for basic research as well as for imaging [62] and therapeutic applications [60].…”
Section: Barnase-barstar Interactionmentioning
confidence: 95%
“…They also designed a scFv-(barnasebarnase) fusion protein (termed 'dibarnase'), in which two barnase units were directly fused head-totail without a linker. This module allowed binding of the scFv Ig to the QDs [61]. Taken together, data has shown that the barnase-barstar system constitutes a useful tool for the design of oligomeric proteins for basic research as well as for imaging [62] and therapeutic applications [60].…”
Section: Barnase-barstar Interactionmentioning
confidence: 95%
“…6 The cells were cultivated in YTPS broth until the stationary growth phase, and then centrifuged, followed by re-suspension in cold lysis buffer [0.05 M Tris-HCl, 0.1 M NaCl, 10 mM ethylenediaminetetraacetic acid (EDTA), 10 mM dithiothreitol (DTT), pH 8.0]. The obtained solution was sonicated on ice with a 30% ammonium sulfate saturation for cell disruption followed by nucleic acid precipitation with poly (ethyleneimine).…”
Section: Protein Production and Characterizationmentioning
confidence: 99%
“…The UCNP signal in vitro was also modeled using Eqs. (5) and (6), with the optical properties of the phantom and I ex ¼ 100 W∕cm 2 as parameters. As is shown in Fig.…”
Section: Theoretical Modeling Of In Vivo Imagingmentioning
confidence: 99%
See 2 more Smart Citations